Development of an Android-Based Inventory Application to Improve Stock Management Efficiency - Herayati; Anus Wuryanto; Dewi Yuliandari; Hari Sugiarto; Widiarina (J-INTECH ( Journal of Information and Technology), 2026)
Advances in information technology are driving companies to implement digital systems to improve operational efficiency, particularly in stock and inventory management. PT Interior Indonesia still uses manual stock recording, which results in data inaccuracies, delays in information, and difficulties in monitoring stock availability in real time. This research aims to design and develop an Android-based mobile application capable of supporting structured, accurate, and efficient stock and inventory management. The research method employed is a qualitative approach through observation, interviews, and literature review, utilising the Rapid Application Development (RAD) software development model. The application was developed using the Flutter framework with Firebase Cloud Firestore as the backend database. The results of the study indicate that the developed application is capable of improving the accuracy of stock recording, accelerating the stock management process, and facilitating real-time monitoring of stock availability. Consequently, this application is expected to support operational efficiency and decision-making at PT Interior Indonesia